Wred: Workload Reduction for Scalable Index Tuning - Brucato, Matteo; Siddiqui, Tarique; Wu, Wentao; Narasayya, Vivek; Chaudhuri, Surajit (Proceedings of the ACM on Management of Data (SIGMOD 2024), 2024)
Modern database systems offer index-tuning advisors that automatically identify a set of indexes to improve workload performance. Advisors leverage the optimizer's what-if API to optimize a query for a hypothetical index configuration. Because what-if calls constitute a major bottleneck of index tuning, existing techniques, such as workload compression, help reduce the number of what-if calls to speed up tuning. Unfortunately, even with small workloads and few what-if calls, tuning can still take hours due to the complexity of the queries (e.g., the number of joins, filters, group-by and order-by clauses), which increases their optimization time. This paper introduces workload reduction, a new complementary technique aimed at expediting index tuning by decreasing individual what-if call time without significantly affecting the quality of index tuning. We present an efficient workload reduction algorithm, called Wred, which rewrites each query in the original workload to eliminate column and table expressions unlikely to benefit from indexes, thereby accelerating what-if calls. We study its complexity and ability to maintain high index quality. We perform an extensive evaluation over industry benchmarks and real-world customer workloads, which shows that Wred results in a 3x median speedup in tuning efficiency over an industrial-strength state-of-the-art index advisor, with only a 3.7% median loss in improvement—where improvement is the total workload cost as estimated by the query optimizer—and results in up to 24.7x speedup with 1.8% improvement loss. Furthermore, combining Wred and Isum (a state-of-the-art workload compression technique for index tuning) results in higher speedups than either of the two techniques alone, with 10.5x median speedup and 5% median improvement loss.